Construction of OFDM M-QAM sequences with low peak-to-average power ratio. - Tarokh, B. (IEEE Transactions on communications)
We present a technique to derive M-quadrature amplitude modulation (QAM) signals from quaternary phase-shift keying (QPSK) constellations when M=2n and n is an even number. By utilizing QPSK Golay sequences, we have constructed M-QAM sequences with low peak-to-mean envelope power ratios. Several upper bounds for these M-QAM sequences were derived.